The Influence of Profitability, Leverage, Tax Planning and Company Size on Profit Management (Empirical Study on Technology Companies registered on JII 70) - Hidayati, Nurul; Fatoni, Ahmad (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem : In Indonesia, there has been a strong increase in the muslim stock market. 60% of issuers listed on the Indonesia Stock Exchange (IDX) fall into the Sharia category. In 2022 several corporate sectors have experienced a decline in shares. The technology sector, one of which fell by 33.24% in the periode 2022.Purpose/Objective Study : This study aimed at determine (1) effect of profitability on earnings management (2) effect of leverage on earnings management (3) effect of tax planning on earnings management (4) effect of company size on earnings managementDesign/Methodology/Approaches : The method used in this research is descriptive qualitative. With a population of all technology companies registered on the Jakarta Sharia Index 70 throughout 2018 - 2022. The sampling technique uses saturated sampling. The data of this research uses secondary data types and is obtained from www.idx.co.idand the company's website. The software used in the panel analysis in this study was Eviews 12.0 and Microsoft Office Excel.Findings : The study found that (1) Profitability is affected by Profit Management (2) Leverage isÂ  affected by Profit Management (3) Tax Planning does not impact Earnings Management (4) the Company size have an influance on Earnings Management.PaperType : Research Articles